Meningomyelocele in a 54-year-old male: A case report of late presentation of voiding symptoms (Indian Journal of Case Reports, 2020)
Meningomyelocele (MMC) is a congenital malformation of the spine, spinal cord, and overlying meninges. The neurologic deficit produced by the MMC can be variable and depends on what neural elements, if any, have everted with the meningocele sac. The neurologic lesion produced by this condition influences the lower urinary tract function in a variety of ways. We report the case of a 54-year-old male with lumbosacral MMC who was asymptomatic till 6 months back and was not treated for MMC. He presented with urinary voiding complaints following a fall and sustaining trauma. The patient underwent excision of MMC with detethering of the cord. Following surgery, the patient continued to have symptoms of the inability to pass urine.